The prescribable drugs with efficacy in experimental epilepsies (PDE3) database for drug repurposing research in epilepsy. (17th January 2018) - Sivapalarajah, Shayeeshan; Krishnakumar, Mathangi; Bickerstaffe, Harry; Chan, YikYing; Clarkson, Joseph; Hampden‐Martin, Alistair; Mirza, Ahmad; Tanti, Matthew; Marson, Anthony; Pirmohamed, Munir; Mirza, Nasir
Summary: Objective: Current antiepileptic drugs (AEDs) have several shortcomings. For example, they fail to control seizures in 30% of patients. Hence, there is a need to identify new AEDs. Drug repurposing is the discovery of new indications for approved drugs. This drug "recycling" offers the potential of significant savings in the time and cost of drug development. Many drugs licensed for other indications exhibit antiepileptic efficacy in animal models. Our aim was to create a database of "prescribable" drugs, approved for other conditions, with published evidence of efficacy in animal models of epilepsy, and to collate data that would assist in choosing the most promising candidates for drug repurposing. Methods: The database was created by the following: (1) computational literature‐mining using novel software that identifies Medline abstracts containing the name of a prescribable drug, a rodent model of epilepsy, and a phrase indicating seizure reduction; then (2) crowdsourced manual curation of the identified abstracts. Results: The final database includes 173 drugs and 500 abstracts. It is made freely available atwww.liverpool.ac.uk/D3RE/PDE3 . The database is reliable: 94% of the included drugs have corroborative evidence of efficacy in animal models (for example, evidence from multiple independent studies). The database includes many drugs that are appealing candidates for repurposing, as they are widely accepted by prescribers and patients—the database includes half of the 20 most commonly prescribed drugs in England—and they target many proteins involved in epilepsy but not targeted by current AEDs. It is important to note that the drugs are of potential relevance to human epilepsy—the database is highly enriched with drugs that target proteins of known causal human epilepsy genes (Fisher's exact test P ‐value < 3 × 10 −5 ). We present data to help prioritize the most promising candidates for repurposing from the database. Significance: The PDE3 database is an important new resource for drug repurposing research in epilepsy.